Manajemen Mutu Pendidikan dalam Upaya Meningkatkan Kemandirian Madrasah - Tahrir Rosadi (LPPM IAINU Kebumen, 2021)
This research was compiled based on the importance of implementing educational quality management in a madrasah. The focus of this research is on the implementation of quality management of eight national education standards. In this regard, research was conducted with the aim of knowing the planning, implementation, evaluation, and follow-up of educational quality management in an effort to increase the independence of madrasah in Indonesia. This study uses qualitative research. Collecting data using observation, interviews, and documentation. The validity of the data using data triangulation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. This study shows that: (1) Planning for education quality management has been carried out properly. Planning begins with a joint meeting to determine the objectives to be achieved through the realization of the program. (2) The implementation of quality management in education has been carried out well. In implementation, the madrasa head is able to move educators to carry out the program according to plan. (3) Evaluation of education quality management has been carried out properly. The head of the madrasa guarantees the implementation of education quality management through supervision and implementation evaluation meetings to look for deficiencies. (4) The follow-up of education quality management has been carried out properly. The madrasa principal uses the basic evaluation stages to determine the follow-up steps to be taken.